Sublingual allergen immunotherapy with a liquid birch pollen product in patients with seasonal allergic rhinoconjunctivitis with or without asthma - Pfaar, Oliver; Bachert, Claus; Kuna, Piotr; Panzner, Petr; Džupinová, Mária; Klimek, Ludger; van Nimwegen, Maroesja J; Boot, Johan D; Yu, Donghui; Opstelten, Dirk Jan E; de Kam, Pieter-Jan (The Journal of allergy and clinical immunology, 2019)
BACKGROUND: Sublingual allergen immunotherapy (SLIT) has been demonstrated to be both clinically efficacious and safe. However, in line with the current regulatory guidance from the European Medicines Agency, allergen immunotherapy (AIT) products must demonstrate their efficacy and safety in pivotal phase III trials for registration. OBJECTIVE: We sought to investigate the efficacy and safety of sublingual high-dose liquid birch pollen extract (40,000 allergy units native [AUN]/mL) in adults with birch pollen allergy. METHODS: A randomized, double-blind, placebo-controlled, parallel-group multicenter trial was conducted in 406 adult patients with moderate-to-severe birch pollen-induced allergic rhinoconjunctivitis with or without mild-to-moderate controlled asthma. Treatment was started 3 to 6 months before the birch pollen season and continued during the season in 40 clinical study centers in 5 European countries. For primary end point assessment, the recommended combined symptom and medication score of the European Academy of Allergy and Clinical Immunology was used. Secondary end points included quality-of-life assessments, immunologic parameters, and safety. RESULTS: Primary efficacy results demonstrated a significant (P < .0001) and clinically relevant (32%) reduction in the combined symptom and medication score compared with placebo after 3 to 6 months of SLIT. Significantly better rhinoconjunctivitis quality-of-life scores (P < .0001) and the patient's own overall assessment of his or her health status, including the visual analog scale score (Euro Quality of Life Visual Analogue Scale; P = .0025), were also demonstrated. In total, a good safety profile of SLIT was observed. CONCLUSION: This study confirmed both the clinical efficacy and safety of a sublingual liquid birch pollen extract in adults with birch pollen allergy in a pivotal phase III trial (EudraCT: 2013-005550-30; ClinicalTrials.gov: NCT02231307).
Keywords: safety; pivotal phase III trial; Sublingual Immunotherapy; Asthma; bronchiální astma; Humans; lidé středního věku; Allergens; combined symptom and medication score; Double-Blind Method; Rhinitis, Allergic, Seasonal; Female; Aged; mladý dospělý; dospělí; výsledek terapie; senioři; alergeny; dvojitá slepá metoda; lidé; allergen immunotherapy; Antigens, Plant; sezónní alergická rýma; Adult; Birch pollen allergy; sublinguální imunoterapie; Betula; ženské pohlaví; Male; Middle Aged; Pollen; alergická konjunktivitida; bříza; Adolescent; Treatment Outcome; sublingual immunotherapy; allergic rhinoconjunctivitis; Young Adult; efficacy; quality of life; pyl; Conjunctivitis, Allergic; mužské pohlaví; antigeny rostlinné; mladiství